The Effect of Work-Life Balance on Psychological Well-Being Among Healthcare Workers in Sumenep - Ningtyas, Wasilatul Fadila; Mulyana, Olievia Prabandini (Universitas Pamulang, 2026)
Healthcare workers are a work group at high risk of experiencing physical and psychological stress, so maintaining psychological well-being is a crucial aspect in preventing stress and burnout. This study aims to determine the effect of work-life balance on psychological well-being among healthcare workers in Sumenep. This study used a quantitative method, with data collected through a Google form. The sample was determined using a census (total sampling) targeting approximately 111 healthcare workers in Sumenep. Furthermore, the data were further analyzed using simple linear regression. The analysis of the study results suggests that work-life balance has a significant influence on psychological well-being, as evidenced by a significance value of p = 0.000. The coefficient of determination of R² = 47.8% indicates that almost half of the variation in psychological well-being can be explained by work-life balance. This analysis explains that the better the WLB possessed by healthcare workers, the higher the level of PWB they feel. This condition can also be seen in the context of the characteristics of the Sumenep region, which differs from urban areas, including in terms of access to support facilities for psychological recovery outside the work environment. These limitations force healthcare workers to rely more heavily on WLB to maintain psychological well-being. Overall, the research findings demonstrate that WLB is a crucial aspect in understanding the PWB of healthcare workers in Sumenep. This study suggests that healthcare facilities in Sumenep need to prioritize flexible work arrangements and psychosocial support, given the limited external coping resources available to healthcare workers.